Pruning of the Pulmonary Vasculature in Asthma. The Severe Asthma Research Program (SARP) Cohort - Ash, Samuel Y.; Rahaghi, Farbod N.; Come, Carolyn E.; Ross, James C.; Colon, Alysha G.; Cardet-Guisasola, Juan Carlos; Dunican, Eleanor M.; Bleecker, Eugene R.; Castro, Mario; Fahy, John V.; Fain, Sean B.; Gaston, Benjamin M.; et al. (American journal of respiratory and critical care medicine, 2018)
Loss of the peripheral pulmonary vasculature, termed vascular pruning, is associated with disease severity in patients with chronic obstructive pulmonary disease. To determine if pulmonary vascular pruning is associated with asthma severity and exacerbations. We measured the total pulmonary blood vessel volume (TBV) and the blood vessel volume of vessels less than 5 mm in cross-sectional area (BV5) and of vessels less than 10 mm (BV10) in cross-sectional area on noncontrast computed tomographic scans of participants from the Severe Asthma Research Program. Lower values of the BV5 to TBV ratio (BV5/TBV) and the BV10 to TBV ratio (BV10/TBV) represented vascular pruning (loss of the peripheral pulmonary vasculature). Compared with healthy control subjects, patients with severe asthma had more pulmonary vascular pruning. Among those with asthma, those with poor asthma control had more pruning than those with well-controlled disease. Pruning of the pulmonary vasculature was also associated with lower percent predicted FEV and FVC, greater peripheral and sputum eosinophilia, and higher BAL serum amyloid A/lipoxin A ratio but not with low-attenuation area or with sputum neutrophilia. Compared with individuals with less pruning, individuals with the most vascular pruning had 150% greater odds of reporting an asthma exacerbation (odds ratio, 2.50; confidence interval, 1.05-5.98; P = 0.039 for BV10/TBV) and reported 45% more asthma exacerbations during follow-up (incidence rate ratio, 1.45; confidence interval, 1.02-2.06; P = 0.036 for BV10/TBV). Pruning of the peripheral pulmonary vasculature is associated with asthma severity, control, and exacerbations, and with lung function and eosinophilia.